Explaining the Unexplained: Residual Wage Inequality, Manufacturing Decline, and Low-Skilled Immigration - Eric D. Gould (Institute for the Study of Labor (IZA), 2015)
This paper investigates whether the increasing "residual wage inequality" trend is related to manufacturing decline and the influx of low-skilled immigrants. There is a vast literature arguing that technological change, international trade, and institutional factors have played a significant role in the inequality trend. However, most of the trend is unexplained by observable factors. This paper attempts to "explain" the growth in the unexplained variance of wages by exploiting variation across locations (states or cities) in the United States in the local level of "residual inequality." The evidence shows that a shrinking manufacturing sector increases inequality. In addition, an influx of low-skilled immigrants increases inequality, but this effect is concentrated in areas with a steeper manufacturing decline. Similar results are found for two alternative measures linked to increasing inequality: the increasing return to education and the decline in the employment rate of non-college men. The overall evidence suggests that the manufacturing and immigration trends have hollowed-out the overall demand for middle-skilled workers in all sectors, while increasing the supply of workers in lower skilled jobs. Both phenomena are producing downward pressure on the relative wages of workers at the low end of the income distribution.
Keywords: J31; 330; inequality; manufacturing; low-skilled immigration